1991
DOI: 10.1099/00221287-137-6-1333
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between gametic differentiation and the cell cycle in the green alga Chlamydomonas eugametos

Abstract: The relationship between the vegetative cell cycle and sexual competence in the green alga Chlamydomonas eugametos was studied using synchronized cultures. The gametic stage was found to be a regular part of the cell cycle; it extended from the beginning of the cell cycle to about 2 h prior to the commitment point for cell division. All variations in the length of this period caused by external growth conditions were accompanied by corresponding changes in the period of mating competence. The period varied dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1992
1992
2000
2000

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…A gametogenic division occurred just before the culture entered stationary phase (Tomson et af., 1985). Recently, zoospores of C. eugametos were described to behave like gametes (Zachleder et al, 1991). The gametic stage was suggested to be a regular part of the cell cycle in synchronous exponen tial-p hase cultures, which were supposedly growing under conditions without nutrient limitation.…”
Section: Mating Competence and Agglutinin Productionmentioning
confidence: 99%
See 3 more Smart Citations
“…A gametogenic division occurred just before the culture entered stationary phase (Tomson et af., 1985). Recently, zoospores of C. eugametos were described to behave like gametes (Zachleder et al, 1991). The gametic stage was suggested to be a regular part of the cell cycle in synchronous exponen tial-p hase cultures, which were supposedly growing under conditions without nutrient limitation.…”
Section: Mating Competence and Agglutinin Productionmentioning
confidence: 99%
“…Interestingly, the onset of excretion of extracellular material coincided with the decrease in growth of the cells. The production of this material preceded the retraction of the flagella and mitosis (Zachleder et al, 1991). Fig.…”
Section: Characterization Of the Cell Cyclementioning
confidence: 99%
See 2 more Smart Citations
“…They showed that synchronized cells transferred to N-free conditions in early G1 became mating competent directly, but cells transferred 6 or 12 h later needed a cell division before H. van den Ende Institute for Molecular Cell Biology, BioCentrum Amsterdam, University of Amsterdam, Kruislaan 318, 1098 SM Amsterdam, The Netherlands; Fax no: +31-20-525-7934 producing gametes. Also, synchronous cells of C. eugametos showed mating competence only during the first part of the cell cycle (Zachleder et al 1991).…”
Section: Introductionmentioning
confidence: 99%